Transformative Inquiry and Production of Islamic Knowledge (American Journal of Islam and Society, 2001)
Transformative inquiry is proposed in this paper as an alternativeresearch method that emerges from the Islamic paradigm and leadsto the creation of Islamic knowledge on one hand and inner selftransformation on the other. The emphasis, however, will beon transformative research methods based on this union of innerexperiences of awakening of the soul from inside and unfolding ofresearch experiences and knowledge from outside. Before doing that,I will shed some light on related issues of conventional and alternativeparadigms such as positivism and constructivism. Also related issuesto transformation, such as wholeness and relationships, are discussed.Finally, four methods of inquiry, are proposed as transformativemethods that have the potential for producing Islamic knowledge.